2022
DOI: 10.1038/s41598-022-08188-y
|View full text |Cite
|
Sign up to set email alerts
|

Echogenic swirling pattern, carcinoembryonic antigen, and lactate dehydrogenase in the diagnosis of malignant pleural effusion

Abstract: The echogenic swirling pattern has a role in predicting malignant pleural effusion (MPE). However, its predictive ability is suboptimal, and its clinical utility remains to be defined. The aim of this study was to assess the diagnostic potential of the echogenic swirling pattern combined with pleural carcinoembryonic antigen (CEA) and routine laboratory tests of pleural effusion in MPE. The 80 consecutive patients with underlying malignancy and pleural effusions were recruited. All patients underwent one diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The model’s most discriminating variable was dyspnoea, which increased the likelihood of the effusion being malignant by 14-fold ( Table 3 ). MPE is linked to a median survival of 3–6 months and can significantly impair quality of life due to severe dyspnoea ( 18 ). Our model included fever and X-ray/CT findings compatible with malignancy, similar to the predictive MPE model proposed by Luis Valdes et al.…”
Section: Discussionmentioning
confidence: 99%
“…The model’s most discriminating variable was dyspnoea, which increased the likelihood of the effusion being malignant by 14-fold ( Table 3 ). MPE is linked to a median survival of 3–6 months and can significantly impair quality of life due to severe dyspnoea ( 18 ). Our model included fever and X-ray/CT findings compatible with malignancy, similar to the predictive MPE model proposed by Luis Valdes et al.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical diagnostic e ciency of sCEA, pCEA, pLDH, and sNSE in the diagnosis of MPE was reportedly satisfactory. (17,18,19,20,21) A large body of work on the function of tumor markers showed that these contributed to the identi cation of MPE. ( 22)However, sSCC levels were ltered out by LASSO regression analysis, which is considered superior to select predictors by univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…[13] Previously, most reported studies were performed using contact B-scans. [14][15][16] Yang et al analyzed sonographic images of 320 patients with pleural effusion. Their results showed that all patients with transudates presented anechoic appearance on ultrasonography (96/96), whereas anechoic effusion could be a TPE or EPE (33.9%).…”
Section: Discussionmentioning
confidence: 99%